Predictors of Diabetes Self-Management Behaviors among Patients with Type 2 Diabetes Mellitus in Aceh, Indonesia - Riski Amalia; Nani Safuni; Aulia Kamal; Anda Kamal; Asrizal; Sri Agustina; Fiona Desi Amelia; Tri Nur Handayani (Caring: Indonesian Journal of Nursing Science, 2026)
Patients managing Type 2 Diabetes Mellitus (T2DM) themselves are still key to reducing morbidity, mortality, and complications. T2DM blood sugar regulation is affected by several internal and environmental factors. This research aims to investigate the extent of factors related to self-management techniques in T2DM patients in Aceh Province, Indonesia. This study employed a cross-sectional predictive correlational design and was conducted in a subdistrict of Banda Aceh. This research sample has used the G*Power program, which indicated that there were 118 T2DM patients. This study utilized a purposive sampling technique. The Diabetes Self-Management Questionnaire (DSMQ), the Diabetes Mellitus Self-Efficacy Scale (DMSES), and the RAND Health Support Questionnaire (RAND SF-36). IBM SPSS Statistics 27 was used to perform the study's multiple linear regression analysis. The findings of this study showed that greater participation in the T2DM management education program was significantly associated with improved self-management behaviors (β = 0.326, p < 0.0001). In contrast, lower levels of family support (β = -0.184, p = 0.030) and self-efficacy (β = -0.172, p = 0.048) were negatively associated with T2DM self-management. The findings of this study showed that greater participation in the T2DM management education program was significantly associated with improved self-management behaviors (β = 0.326, p < 0.0001). In contrast, lower levels of family support (β = -0.184, p = 0.030) and self-efficacy (β = -0.172, p = 0.048) were negatively associated with T2DM self-management behaviors. For this research, a continuous T2DM self-management education program for families and counselor nurses is recommended. Keyword: Family Support, Self-Efficacy, Self-Management, T2DM